Impact of Job Skills Training Programs on Urban Poverty - Suparmono (Faculty of Economics and Business, University of Pancasakti Tegal, 2021)
The aim of this study is to examine the effect of the ready-to-work skills training offered by the Republic of Indonesia's Ministry of Social Affairs on urban poor people who are members of micro and small businesses to mitigate urban poverty. This research was conducted in Balikpapan City during the 2019 season. The empirical approach used is statistics that are descriptive. Data collection was performed by telephone interviews with job skills training program recipients. As a result, in the form of growing skills, the training programs offered to the urban poor and some micro and small enterprises had a positive effect and those who did not pursue their business were able to find work due to the training they got. The flaw of this preparation is linked to the training recipients' continuous level of ability such that they are not yet at the advanced level.